Analysis of Malondialdehyde (MDA) Levels Based on Body Mass Index, Waist Circumstances, and Body Fat Percentage in Students of Medicine Program Faculty of Medicine Mataram University - Ida Ayu Eka Widiastuti; Fitriannisa Faradina Zubaidi; Basuki Rahmat; Gede Wira Buanayuda (Jurnal Biologi Tropis, 2022)
Obesity can cause chronic oxidative stress. Oxidative stress occurs when the formation of free radicals is greatly increased or the protective antioxidant mechanisms are disrupted. Previous studies have concluded that there is a relationship between oxidative stress and excess body weight and obesity. One of the products of oxidative stress is malondialdehyde (MDA). This study aims to determine the correlation between malondialdehyde (MDA) levels and body mass index (BMI), waist circumference (LP), and body fat percentage. The subjects were 55 students of the Medical Education Study Program, Faculty of Medicine, University of Mataram, class of 2021. The BMI variable was calculated by dividing body weight (kg) by the square of height (m), waist circumference was measured using a tape measure (cm), and body fat percentage measured by body composition monitor (%). Serum MDA levels were measured using the ELISA method. Data were analyzed statistically with the Spearman correlation test. The results showed that the average MDA level in subjects with overweight and obesity was higher than normal, however there was no significant correlation between body mass index, waist circumference, and body fat percentage with MDA levels, with each significance value :p=0.230; p=0.276; and p=0.666. Body mass index, waist circumference, and body fat percentage cannot be ruled out as risk factors for oxidative stress.